COMPREHENSIVE PHYTOCHEMICAL ANALYSIS AND THERAPEUTIC EVALUATION OF ACALYPHA FRUTICOSA LEAVES IN TYPE I DIABETIC RATS - Suri CR; AMOL S RAKTE; CHANDANAM SREEDHAR; HARSHA K TRIPATHY; CHOUDHURY PK; DEEPAK KUMAR JHA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The study evaluates the safety, phytochemical composition, and effectiveness of Acalypha fruticosa leaf extracts in managing Type I diabetes in rats. Methods: The methodology involves collecting and verifying plant materials, preparing methanolic extracts, identifying phytochemicals, and determining morphological characteristics. Protective effects are assessed through monitoring body weight, feed, and water consumption, measuring plasma glucose and insulin levels, evaluating lipid peroxidative markers, assessing antioxidant activities, measuring inflammation-related cytokines, assessing liver health, and evaluating the impact on alpha-amylase glycogen levels. Histopathological study is also conducted to observe structural changes and protective effects. The aim is to provide a comprehensive evaluation of the efficacy and safety of A. fruticosa leaves extracts in managing Type I diabetes. Results: Methanolic extract of A. fruticosa (MeAF) (A. fruticosa) was effective in preventing weight loss, with the higher dose (500 mg/kg) being particularly effective in maintaining body weight. MeAF 250 mg/kg moderately prevented weight loss and improved insulin levels, while MeAF 500 mg/kg significantly reduced blood glucose levels and improved various biomarkers in a dose-dependent manner. MeAF increased catalase activity and restored superoxide dismutase and glutathione levels, showing strong antioxidant potential similar to insulin. MeAF reduced inflammatory markers and showed moderate liver protection, with the higher dose being more effective in reducing alkaline phosphatase, serum glutamate pyruvate transaminase, and serum glutamic oxaloacetic transaminase levels. STZ-induced diabetic rats showed a significant elevation in serum α-amylase levels, whereas treatment with MeAF exhibited a dose-dependent reduction. Similarly, MeAF improved liver glycogen levels and restored plasma vitamin C, with 500 mg/kg producing effects comparable to those observed with insulin. MeAF preserved pancreatic structure with no significant damage to islets or acini at the higher dose, suggesting protective effects against diabetes-induced damage. Conclusion: A. fruticosa (MeAF) has shown promising potential in managing diabetes and its complications. It improves glucose metabolism, reduces oxidative stress, and provides moderate protection to pancreatic and liver tissues in diabetic rats. MeAF could serve as a natural, complementary therapy, especially in areas with limited access to conventional treatments.